Denial of justice in international law - Paulsson, Jan (Hersch Lauterpacht memorial lectures, 2005)
"Denial of justice is one of the oldest bases of liability in international law and the modern understanding of denial of justice is examined by Paulsson in this book. The possibilities for prosecuting the offence of denial of justice have evolved in fundamental ways and it is now settled law that States cannot disavow international responsibility by arguing that their courts are independent of the government. Even more importantly, the doors of international tribunals have swung wide open to admit claimants other than states: non-governmental organisations, corporations, and individuals, and Paulsson examines several recent cases of great importance in his book. "-- Provided by publisher